Sistem Informasi Akuntansi Peminjaman Dan Pembayaran Angsuran Berbasis Web Pada Kantor Unit Pengelolaan Kegiatan (UPK) Sejangkung - Aulia Hidayah; Muhamad Syarif; Latifah Latifah; Nurmalasari Nurmalasari (LPPM Universitas Bina Sarana Informatika, 2022)
In the economic field the need for financial information is indispensable. In line with the mobility of complex financial transactions, fast and accurate management of data and information is required. Utilization of technology applied in various business fields with large, medium and small scale. One example of the application of information in the financial field is the office of the Activity Management Unit (UPK) is a business activity in the form of a loan saving service that empowers rural communities independently to alleviate poverty in accordance with the mandate of the National Program for Independent Community Empowerment (PNPM). In today's technology era, a service for the village has been widely used and utilized information technology to make the service process easier, transparent and faster. Therefore, in this research we have the opportunity to develop a web-based loan and installment payment information system in the development of this system we use php programming language, this system will have several features, such as processing data such as loan transaction data, installment transactions, member data, group data, job title data and can access the account settings menu. Outputs generated in this information system such as loan reports, installment reports, and member data reports. The result of this research is the village service information system that can help the work of employees at UPK Sejangkung Sambas masalah recording borrowing and installment payments that are still recorded manually so as to slow down the processing of files and the process of recording reports.